2000
DOI: 10.1016/s0378-1127(99)00116-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of shaded fuelbreaks in landscape fire management

Abstract: Shaded fuelbreaks and larger landscape fuel treatments, such as prescribed ®re, are receiving renewed interest as forest protection strategies in the western United States. The effectiveness of fuelbreaks remains a subject of debate because of differing fuelbreak objectives, prescriptions for creation and maintenance, and their placement in landscapes with differing ®re regimes. A well-designed fuelbreak will alter the behavior of wildland ®re entering the fuel-altered zone. Both surface and crown ®re behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
214
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(233 citation statements)
references
References 10 publications
2
214
1
1
Order By: Relevance
“…Modification of any of these fuel strata by silvicultural operations will thus have implications for fire behaviour, severity and suppression effectiveness (Peterson et al, 2005). Mature even-aged stands are usually more resistant to fire than multi-layered or young stands (Agee et al, 2000;Fernandes and Rigolot, 2007;González et al, 2007b;Omi and Martinson, 2004;Pollet and Omi, 2002), and have lower probability of being affected by fire (González et al, 2006). Thus, regeneration methods that drive the development of stands to even-aged structures (clear cuttings followed by planting or very intense shelterwood methods) are expected to reduce susceptibility to fire.…”
Section: Regeneration Methodsmentioning
confidence: 99%
“…Modification of any of these fuel strata by silvicultural operations will thus have implications for fire behaviour, severity and suppression effectiveness (Peterson et al, 2005). Mature even-aged stands are usually more resistant to fire than multi-layered or young stands (Agee et al, 2000;Fernandes and Rigolot, 2007;González et al, 2007b;Omi and Martinson, 2004;Pollet and Omi, 2002), and have lower probability of being affected by fire (González et al, 2006). Thus, regeneration methods that drive the development of stands to even-aged structures (clear cuttings followed by planting or very intense shelterwood methods) are expected to reduce susceptibility to fire.…”
Section: Regeneration Methodsmentioning
confidence: 99%
“…Additionally, on south facing slopes fuel moisture is lower for a longer period each year than on north facing slopes increasing the likelihood of an ignition developing into a fire (Agee 1993). Fires may also burn again sooner in pine dominated forests since the production of fine fuel is greater in pine versus fir dominated mixed conifer forests (e.g., Agee andothers 1978, Stohlgren 1988).…”
Section: Landscape Scale Variationmentioning
confidence: 99%
“…Thinning in these areas reduces canopy cover to 40% by evenly spacing leave trees and separating their crowns. Research, however, has suggested there is limited reduction in crown fire potential through overstory thinning and tree crown separation (Agee et al 2000;Butler et al 2004, Agee andSkinner 2005). Furthermore, studies in active fire regime forests (Stephens and Fry 2004;Stephens and Gill 2005), and stand reconstructions (Bonnicksen and Stone 1982;North et al 2007) indicate forest structures (live trees, snags, logs and regeneration) were highly clustered in forests with frequent lowintensity fire.…”
Section: Western Mixed-conifer Forestsmentioning
confidence: 99%